Living conditions and health contexts. A territorial analysis applied to the Argentine population (2001 – 2010) (Huellas, 2020)
In recent years, the academic field has been improved by numerous contributions related to the concept and measurement of population well-being. Among such improvements, the concept of living conditions has played a central role. In this paper we observe the associations between living conditions and relate this concept to the notion of health contexts based on an eco-epidemiological model. For this purpose, a methodological proposal was developed and applied to the Argentine population, identifying areas of improvement, worsening and persistence of living conditions between 2001 and 2010. Finally, the proposal was validated with a classic indicator of poverty measurement and the course of living conditions was analyzed in the most critical jurisdictions of the territory through the use of an infant mortality indicator that operates on the concept of “poverty diseases”.
Keywords: living condition; health context; poverty; territorial differences